Integrating Medical Simulation into Residency Programs in Kingdom of Saudi Arabia - Alzoraigi,Usamah; Almoziny,Shadi; Almarshed,Abdullah; Alhaider,Sami (Advances in Medical Education and Practice, 2022)
Usamah Alzoraigi,1 Shadi Almoziny,1 Abdullah Almarshed,1 Sami Alhaider1,2 1Center of Research, Education Simulation and Enhanced Training (CRESENT), King Fahad Medical City, Riyadh, Saudi Arabia; 2Executive Presidency of Academic Affairs, Saudi Commission for Health Specialties, Riyadh, Saudi ArabiaCorrespondence: Usamah Alzoraigi, Center of Research, Education Simulation and Enhanced Training (CRESENT), King Fahad Medical City, Riyadh, 11525, Saudi Arabia, Tel +966 505104548, Email dr.usamah@gmail.comPurpose: This study conducted a simulation needs assessment on diverse ongoing residency training programs supervised by the Saudi Commission for Health Specialties (SCFHS) in Saudi Arabia. The goal was to develop a standardized methodological approach to integrate simulation as a teaching tool for any ongoing training program.Methods: A mixed-methods approach is used in four steps to focus on top educational needs and integrate simulation into the curriculum. The first step was the selection of 38 residency training programs based on the scoring criteria tool. Of these, nine were selected as target programs. The next step was champion recruitment, where two faculty representatives from each specialty were trained to become specialty champions. The third step was a targeted audience needs assessment, consisting of four phases: curriculum review; a targeted audience survey; stakeholders’ interview; and selection of top educational requirements generated by the first three phases. Lastly, the fourth step used an integration simulation sheet to build common themes for incorporating simulation into the program curriculum.Results: Out of 38 programs, the nine selected top-ranked specialties completed the process, and roadmaps were developed. Using the combined list of all skills and behaviors, the final score proportion was calculated and then ranked. A list of the top needed skills and behaviors was compiled as follows: Obstetrics and Gynecology 10/84, Emergency Medicine (ER) 80/242, Intensive Care Unit 20/139, ...